Trubar’s "Common Language" as the Basis for the First Slovenian Literary Norm - Jesenšek, Marko (Slavia Centralis, 2020)
"Gmajn" literary language is based on the spoken language, which was familiar to Trubar from the Lower Carniola region. However, he upgraded it with Upper Carniolan, and with the language spoken in Ljubljana. "Gmajn" language is a synonym for Carniolan Language (kranjski jezik) which is known as being universally comprehensible. At the same time, "Gmajn" language is a language compromise for the Central Slovene Standard Language.